2010
DOI: 10.1007/s11325-010-0431-7
|View full text |Cite
|
Sign up to set email alerts
|

A videoendoscopic evaluation of the upper airway in South East Asian adults with obstructive sleep apnea

Abstract: Videoendoscopy utilizing flexible nasopharyngolaryngoscopy and Scion Image software is reliable, minimally invasive, and useful as an office procedure in evaluating the multilevel obstruction of upper airway in OSA patients. The retropalatal region has more severe obstruction compared with retroglossal region either in erect or supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In contrast, a study of 57 patients using endoscopy and catheter combined with nasal airway positive pressure and muscle paralysis found that a majority of obstruction occurred in the velopharynx 9. A study of 59 patients using flexible nasopharyngoscopy in seated erect and supine position showed that 49.2% had retropalatal obstruction and 38.9% had both retropalatal and retroglossal obstruction 21. There was a study using fiberoptic nasopharyngoscopy that enrolled 248 patients and showed that four basic patterns of TB narrowing occurred in awake adult patients diagnosed with OSA: high TB type (8.9%), high TB with retroepiglottic narrowing type (15.3%), diffuse TB narrowing type (31.9%), and isolated retroepiglottic narrowing type (41.9%) 22.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, a study of 57 patients using endoscopy and catheter combined with nasal airway positive pressure and muscle paralysis found that a majority of obstruction occurred in the velopharynx 9. A study of 59 patients using flexible nasopharyngoscopy in seated erect and supine position showed that 49.2% had retropalatal obstruction and 38.9% had both retropalatal and retroglossal obstruction 21. There was a study using fiberoptic nasopharyngoscopy that enrolled 248 patients and showed that four basic patterns of TB narrowing occurred in awake adult patients diagnosed with OSA: high TB type (8.9%), high TB with retroepiglottic narrowing type (15.3%), diffuse TB narrowing type (31.9%), and isolated retroepiglottic narrowing type (41.9%) 22.…”
Section: Discussionmentioning
confidence: 96%
“…Surgery is more likely [7] performed the first endoscopic evaluation of dynamic changes of the pharynx with MM in awake patients with OSAHS. In addition to static narrowing, dynamic narrowing of the retropalatal and retroglossal regions contributes to the pathophysiology of OSAHS [19]. FNMM is widely used to evaluate the UA before surgery to improve patient selection and predict outcome and postoperative changes in the UA [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that the upper airway collapse at multiple levels in different degrees contributed to the overall resistance of the upper airway in OSAHS [41][42][43][44][45] . We also observed the hypertrophy of corpus linguae in 15 patients with severe OSAHS and 4 patients with mild-moderate OSAHS.…”
Section: Discussionmentioning
confidence: 99%